Integrating port and social functions in urban public space: A case study of Port Węglowy in Wrocław - Adamiczka, Hanna (Integracja funkcji portowych i społecznych w miejskiej przestrzeni publicznej: studium przypadku Portu Węglowego we Wrocławiu, 2024)
Aim: The study aimed to identify the needs and preferences of Wrocław residents regarding the development of Port Węglowy, the only yacht port in the city wholly owned and managed by the Municipality. The research focused on understanding residents’ vision for the area, assessing its current image, and exploring how the port could combine recreational, social, and port functions to enhance its value as a public space. Methodology: The research used desk research of literature, legal documents, and press materials. An in-depth individual interview (IDI) was conducted with the river policy coordinator in Wrocław. An online survey (CAWI, n = 122) was also administered based on assumptions of the Project for Public Spaces organisation. The survey examined accessibility, comfort and image, functions and activities, and social value. Results: The survey revealed limited awareness of Port Węglowy among Wrocław residents, with a significant portion expressing unfamiliarity with its location and purpose. Many respondents identified issues with accessibility, particularly regarding parking and pedestrian access. The majority of respondents wished to preserve the port character of the area. Preferred amenities included a small watercraft rental and a city beach, while land-based functions like food services and relaxation spaces were the most popular. Respondents generally rated the aesthetic quality of the port as average, with concerns about cleanliness and infrastructure. Implications and recommendations: The findings underscore the potential of Port Węglowy as a multi-functional public space but highlight the need for broader public awareness and engagement. The lack of awareness about the port indicates an opportunity for the Municipality to connect residents more closely with this location, primarily through strategic marketing and community outreach. Recommendations to enhance Port Węglowy’s role as a social and recreational space connected with the port’s functions: 1. Conduct a public awareness campaign to increase knowledge and engagement around Port Węglowy. 2. Hold public consultations with diverse stakeholders, including local residents, city-wide users, and sailors, to ensure all stakeholders’ needs are addressed. 3. Improve accessibility, especially regarding parking and pedestrian routes, and enhance the overall aesthetic and functionality of the port area by introducing small-scale infrastructure. 4. Develop recreational facilities that align with residents’ preferences to increase the port’s social value and appeal. 5. Enhanced infrastructure and aesthetics. Originality/value: This study contributes to the research on integrating port functions within urban public spaces, especially for smaller yacht ports like Port Węglowy in Wrocław. By focusing on resident perceptions and specific local needs, the research highlights the potential of yacht ports to serve as multifunctional spaces that combine social, recreational, and utilitarian roles within a city. The findings underscore the value of involving local communities in the planning and development of such spaces, providing insights that can guide future revitalisation projects in Wrocław and similar urban contexts.
Biblioteka Regionalisty = Regional Journal, 2024, Nr 24, s. 1-11
Keywords: Dolny Śląsk